Solvent-free synthesis of jasminaldehyde over chitosan–layered double hydroxide catalyst assisted by microwave irradiation - Jamal Houssaini; Mohammed Naciri Bennani; Said Arhzaf; Chadia Mounir; Marwa Alaqarbeh; Hammou Ahlafi; Abdellatif Amhoud (Arabian Journal of Chemistry, 2023)
This research paper reports on the use of chitosan-modified layered double hydroxide (LDH) composite catalysts (CS/MgAl–NO3) for the synthesis of jasminaldehyde under microwave irradiation. The catalysts were prepared by co-precipitation in an inert nitrogen atmosphere. The resulting samples were characterized by mean of X–ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), thermogravimetric/differential thermal analysis (TGA/DTA), scanning electron microscope (SEM) with energy-dispersive X–ray (EDX), and N2 adsorption/desorption isotherm (BET) analysis. The basicity of each catalyst was determined by the acid-base titration method. The performance of the catalysts was evaluated in the solvent-free synthesis of jasminaldehyde from aldol by condensation reaction between benzaldehyde and 1–heptanal in a microwave oven at P = 100 W and T = 90 °C. The effects of different parameters that are involved in the reaction, such as the catalyst amount and the benzaldehyde to 1–heptanal molar ratio, and reaction temperature, are investigated in detail. The results showed that the CS-functionalization of the catalyst leads to the enhancement of its basic sites making it more efficient than the naked MgAl–NO3 catalyst, in terms of the initial reaction rate, the conversion of the reactants and the selectivity toward the jasminaldehyde. The CS/MgAl–NO3 catalyst was also evaluated in successive regeneration reaction cycles.